PENERAPAN MODEL PEMBELAJARAN JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS SISWA KELAS 9.4 SMP NEGERI 4 MUARA ENIM - Heriyadi (Bajang Institute, 2022)
This study aims to improve the reading competence of grade 9.4 students of SMP Negeri 4 Muara Enim for the 2019/2020 academic year by applying the Jigsaw technique cooperative learning model. This study applies a class action research model implemented in two cycles, each of which consists of two meetings. Each cycle applies the stages of planning, execution of actions, observation and reflection. The subjects in this study were 30 grade 9.4 students of SMP Negeri 4 Muara Enim. An indicator of the success of this study if at least 70% of grade 9.4 students can achieve scores with the Minimum Completion Criteria (KKM≥70). The results of the study in cycle II showed that with the application of the cooperative learning model, the Jigsaw technique was proven to improve student English learning outcomes. Although in the first cycle the average score achieved by students was 68.20 and only 17 students (57%) had achieved KKM≥70, but in cycle II the average score achieved was 74.10 with 22 students (73%) who had reached KKM≥70.